Plasma Non-Transferred Arc Cladding of Alumina Powder on Mild Steel-Parameters Optimization Using Taguchi Method - Bushroa, A.R.; Ying, C.C. (Trans Tech Publications, 2008)
This research described the optimization of the process parameters for clad coating of alumina (Al2O3) powder on AISI 1018 mild steel utilizing plasma non-transferred arc cladding process using Taguchi method and Pareto ANOVA analysis. Four factors were selected which were plasma arc current, plasma torch velocity, distance between nozzle and layer and ratio of alumina powder to binder. The analysis of the results showed that the optimal combination for high microhardness were distance between nozzle and layer at 3 mm and plasma torch velocity at 0.03 mm.